The Effect of Inflation, Gold Prices in the World, and Operating Revenues to the Lending Rahn at PT Pegadaian (Persero) in Indonesia - Fida Arumingtyas (International Journal of Business and Applied Economics, 2023)
The aim of the study is to examine how PT Pegadaian (Persero)'s rahn reacts to changes in inflation rates, gold prices, and operational income in Indonesia. The EVIEWS 10 analysis software is used to do multiple linear regression analysis (ordinary least square) and classical assumption testing on the hypotheses. Time series data from 2014-2019 are utilized for this analysis. A t-statistic of 0.0014 indicates that inflation rates have a considerable influence on credit rahn, while t-statistics of 0.0000 and 0.0152 indicate that operational revenues and gold price both have significant effects on lending rates. With a coefficient of determination (R2 adj) of 99.5% and the remaining 0.5% impacted by other factors, it can be said that all independent variables influence the lending rahn at PT Pegadaian (Persero).